2008
DOI: 10.1091/mbc.e08-05-0467
|View full text |Cite
|
Sign up to set email alerts
|

All in One:Leishmania majorSTT3 Proteins Substitute for the Whole Oligosaccharyltransferase Complex inSaccharomyces cerevisiae

Abstract: The transfer of lipid-linked oligosaccharide to asparagine residues of polypeptide chains is catalyzed by oligosaccharyltransferase (OTase). In most eukaryotes, OTase is a hetero-oligomeric complex composed of eight different proteins, in which the STT3 component is believed to be the catalytic subunit. In the parasitic protozoa Leishmania major, four STT3 paralogues, but no homologues to the other OTase components seem to be encoded in the genome. We expressed each of the four L. major STT3 proteins individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Mammalian and yeast OST are multisubunit complexes whose catalytic subunit is STT3 (23). We expressed Leishmania major STT3D, a single-subunit OST of broad-range specificity (24). This OST would not be inhibited by the accumulation of triglucosylated proteins as its natural substrate is M7, the main glycan transferred in those parasites (25).…”
Section: Insights To the Molecular Basis Of Glycosylation Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian and yeast OST are multisubunit complexes whose catalytic subunit is STT3 (23). We expressed Leishmania major STT3D, a single-subunit OST of broad-range specificity (24). This OST would not be inhibited by the accumulation of triglucosylated proteins as its natural substrate is M7, the main glycan transferred in those parasites (25).…”
Section: Insights To the Molecular Basis Of Glycosylation Disordersmentioning
confidence: 99%
“…The possibility existed, however, that hypoglycosylation of other protein(s) may be responsible for the observed phenotypes. Expression in the ER of ⌬alg6 S. pombe mutants of L. major STT3, a subunit with a broad range of substrate specificity that was able to replace the whole OST complex in S. cerevisiae (24,32), was able to revert the hypoglycosylation produced in such a strain. However, its expression did not result in a reversion of the defects in the ⌬gls1-S mutants caused by accumulation of G3M9 NLOs (Fig.…”
Section: Insights To the Molecular Basis Of Glycosylation Disordersmentioning
confidence: 99%
“…In addition, the protists Leishmania major and Trypanosoma brucei were found to contain only the Stt3 subunit of OT but are still capable of N -linked glycosylation (5961). In a recent study, the Stt3 homologs in Leishmania major were shown to complement a deletion of the stt3 gene in S. cerevisiae ; however, these proteins did not incorporate into the native yeast OT complex but instead formed a functional homodimer in the cell (59). Although structural studies of the entire OT complex are currently lacking, recent progress has been made towards understanding the proximity of the subunits to one another.…”
Section: N-linked Glycosylation In Eukaryotesmentioning
confidence: 99%
“…Such methods will be needed to create bacterial OTase variants that efficiently glycosylate minimal N-X-S/T acceptor sites. Alternatively, novel bacterial OTases with distinct properties 6 or single-subunit eukaryotic OTases 25 could prove useful. Overall, the engineering of defined glycosylation pathways in E. coli sets the stage for further engineering of this host for the production of vaccines and therapeutics with even more structurally complex human-like glycans.…”
mentioning
confidence: 99%